Efficient hydrogenation of organic carbonates, carbamates, and formates indicates alternative routes to methanol based on CO2 and CO - Balaraman, Ekambaram; Gunanathan, Chidambaram; Zhang, Jing; Shimon, Linda J. W.; Milstein, David (Nature Chemistry, 2011)
Catalytic hydrogenation of organic carbonates, carbamates and formates is of significant interest both conceptually and practically, because these compounds can be produced from CO2 and CO, and their mild hydrogenation can provide alternative, mild approaches to the indirect hydrogenation of CO2 and CO to methanol, an important fuel and synthetic building block. Here, we report for the first time catalytic hydrogenation of organic carbonates to alcohols, and carbamates to alcohols and amines. Unprecedented homogeneously catalysed hydrogenation of organic formates to methanol has also been accomplished. The reactions are efficiently catalysed by dearomatized PNN Ru(II) pincer complexes derived from pyridine- and bipyridine-based tridentate ligands. These atom-economical reactions proceed under neutral, homogeneous conditions, at mild temperatures and under mild hydrogen pressures, and can operate in the absence of solvent with no generation of waste, representing the ultimate ‘green’ reactions. A possible mechanism involves metal–ligand cooperation by aromatization–dearomatization of the heteroaromatic pincer core.

Electron-rich PNP- and PNN-type Ru(II) hydrido-borohydride complexes. synthesis, structure and catalytic activity towards dehydrogenation of alcohols and hydrogenation of esters - Zhang, Jing; Balaraman, Ekambaram; Leitus, Gregory; Milstein, David (Organometallics, 2011)
Electron-rich PNP- and PNN-type ruthenium(II) hydrido borohydride pincer complexes, [RuH(BH4)(tBu-PNP)] (tBu-PNP = (2,6-bis(di-tert-butylphosphinomethyl)pyridine) (5) and [RuH(BH4)(tBu-PNN)] (tBu-PNN = 2-di-tert-butylphosphinomethyl-6-diethylaminomethylpyridine) (6), were prepared from their corresponding N2-bridged dinuclear Ru(II) complexes [(tBu-PNP)RuCl2]2(μ-N2) (3) and [(tBu-PNN)RuCl2]2(μ-N2) (4), respectively. The X-ray structure of 5 reveals a BH4– anion η2 coordinated to ruthenium through two bridging hydrides. A variable-temperature 1H NMR study of 6 exhibits interesting fluxional behavior of the BH4– ligand. Similarly, the Ru(II) hydrido borohydride complex 9, in which the BH4– moiety is coordinated in a η1 bonding mode, was obtained by reaction of [RuCl2(PPh3)(iPr-PNP)] (iPr-PNP = 2,6-bis(diisopropylphosphinomethyl)pyridine) (8) with two equivalents of NaBH4 at room temperature. The hydrido borohydride pincer complexes 5, 6, and 9 catalyze the acceptorless dehydrogenative coupling of primary alcohols to esters and the dehydrogenation of secondary alcohols to the corresponding ketones, accompanied by evolution of hydrogen gas. The reactivity follows the order 6 > 9 > 5. With the hydrido borohydride complex 6 as catalyst, high yields (up to 98%) and high turnover numbers (TON ∼1000) were obtained in the dehydrogenation of primary alcohols under mild and neutral conditions. In addition, 6 effectively catalyzes the hydrogenation of nonactivated aromatic and aliphatic esters to the corresponding alcohols with TON ∼200 under a relatively mild pressure of dihydrogen and neutral and homogeneous conditions. Thus, an efficient homogeneous catalytic system for the dehydrogenation–hydrogenation reactions of alcohols is developed, which is relevant to the current interest in hydrogen storage.

Novel ruthenium complexes and their uses in processes for formation and/or hydrogenation of esters, amides and derivatives thereof - Milstein, David; Balaraman, Ekambaram; Gunanathan, Chidambaram; Gnanaprakasam, Boopathy; Zhang, Jing (EP2629889A2, US9045381, US20130281664, WO2012052996A2, WO2012052996A3, 2012)
The present invention relates to novel Ruthenium complexes and related borohydride complexes, and their use for (1) hydrogenation of amides (including polyamides) to alcohols and amines; (2) preparing amides from alcohols with amines (including preparing polyamides (e.g., polypeptides) by reacting dialcohols and diamines or by polymerization of amino alcohols); (3) hydrogenation of esters to alcohols (including hydrogenation of cyclic esters (lactones), cyclic di-esters (di-lactones) or polyesters); (4) hydrogenation of organic carbonates (including polycarbonates) to alcohols and of carbamates (including polycarbamates) or urea derivatives to alcohols and amines; (5) dehydrogenative coupling of alcohols to esters; (6) hydrogenation of secondary alcohols to ketones; (7) amidation of esters (synthesis of amides from esters and amines); (8) acylation of alcohols using esters; (9) coupling of alcohols with water to form carboxylic acids; and (10) dehydrogenation of beta-amino alcohols to form pyrazines. The present invention further relates to novel uses of certain pyridine Ruthenium complexes.

Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.

Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.